FAK and WNT Signaling: The Meeting of Two Pathways in Cancer and Development - Fonar, Yuri; Frank, Dale (Anti-Cancer Agents in Medicinal Chemistry, 2011)
Recent studies connect the FAK and Wnt/β-catenin signaling pathways, both which promote cancer when aberrantly activated in mammalian cells. Over-stimulation of either Wnt/β-catenin or FAK activities was independently shown to promote numerous types of human cancers, including colon, breast, prostate and ovary. Observations in different model systems suggest a complex and dynamic cross-talk between these two pathways. During early vertebrate development, FAK protein is required for the proper regulation of Wnt/β- catenin signaling that controls pattern formation in the developing nervous system. In Xenopus laevis embryos, FAK protein depletion eliminated Wnt3a gene expression in the neural plate. In mouse osteoclast cells, mechanical stimulation through FAK activation stabilized β-catenin protein to promote its nuclear translocation. In contrast, in the mouse intestine, FAK activity was induced downstream of Wnt to promote intestinal regeneration and was also essential for tumorigenesis in an APC deletion model of colorectal cancer. Adding to this complexity, in human cell lines, FAK induced a context-dependent modulation of Wnt signaling to activate target-gene expression. Other diseases are also associated with FAK and Wnt pathway over-activation. Increased FAK and Wnt pathway activities were independently implicated in idiopathic pulmonary fibrosis (IPF), a lung disease of unknown etiology. Revealing the FAK-Wnt connection in IPF could provide a better understanding of disease pathology. There appear to be multiple interactions between the Wnt/β-catenin and FAK signaling pathways in different cell types and organisms. Mutual FAK-Wnt pathway regulation could be a general phenomenon, having many still undetermined roles in either normal physiological or disease processes.
Keywords: short-term proliferation